Avaliação farmacoeconômica dos tratamentos para leishmaniose visceral no Estado de Sergipe - Santos, João Luiz Alves dos (2015)
Search for new therapeutic alternatives for leishmaniasis is considered essential by the World Health Organization, due to the high toxicity of the drugs currently used, its high cost and the risk of resistance. In Brazil, it is used three drugs to treat leishmaniasis: meglumine antimoniate and two formulations of amphotericin B (deoxycholate and liposomal). This study is a piggy-back evaluation linked to a multicentric clinical trial with the objective to perform a decision analysis between the treatment regimens for visceral leishmaniasis, for both adults and children. For this end, it was performed analysis of the data obtained in the state of Sergipe from 62 patients randomized to treatment with meglumine antimoniate (group A), considered the first line treatment in Brazil, amphotericin B deoxycholate (group B), liposomal amphotericin B (group C) and the combined regimen of meglumine antimoniate with liposomal amphotericin B (group D), in order to conduct a decision analysis from among these therapeutic regimens for both adults and children. To this end, two scenarios were considered: scenario 1 is the currently prevailing in Brazil, where patients are always treated as possible on an outpatient basis with meglumine antimoniate, although with a smaller monitoring on its potentially lethal side effects and a possible lower adherence to treatment. In the scenario 2, patients are hospitalized during the treatment period, with a better monitoring of clinical and laboratory parameters of the patient, although with a higher risk of nosocomial infections and increasing treatment costs. In terms of security, there is an emphasis on amphotericin B deoxycholate as the one that presents a greater amount of serious and potentially lethal adverse reactions, with an average of 2 severe reactions per patient. From the viewpoint of cost-efficacy, for scenario 1 the meglumine antimoniate remains the treatment of choice for both adults and children. However, in scenario 2, the combination of drugs (group D) presented itself as the most costeffective for both adults and children. From this study it became clear, from a safety point of view for the patient, the need to evaluate both therapeutic regimens, particularly amphotericin B deoxycholate, such as the treatment scenarios for visceral leishmaniasis.